2022
DOI: 10.26444/aaem/154827
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencephalitis and postinflammatory hydrocephalus in the course of COVID-19 disease in newborn – the potential role of acetazolamide as add-on therapy to the standard treatment

Abstract: Wątroba SJ, Bryda J. Meningoencephalitis and postinflammatory hydrocephalus in the course of COVID-19 disease in newborn -the potential role of acetazolamide as add-on therapy to the standard treatment. Ann Agric Environ Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…10) Seizures of variable types are common among the more con crete neurological events. 9,24,28,30,49,[88][89][90][91][92][93][94][95][96][97] As expected, some are particularly detailed as febrile seizures. 24) In a large American multi center surveillance study, neonatal COVID-19 was accom panied by a 1.9% frequency of seizures; the frequency did not differ significantly between severe and non-severe patient groups.…”
Section: Manifestations Of Infant Infectionsupporting
confidence: 64%
See 2 more Smart Citations
“…10) Seizures of variable types are common among the more con crete neurological events. 9,24,28,30,49,[88][89][90][91][92][93][94][95][96][97] As expected, some are particularly detailed as febrile seizures. 24) In a large American multi center surveillance study, neonatal COVID-19 was accom panied by a 1.9% frequency of seizures; the frequency did not differ significantly between severe and non-severe patient groups.…”
Section: Manifestations Of Infant Infectionsupporting
confidence: 64%
“…It is also not apparent if the collations and their proportionalities are influenced by selection bias, but the proportion of infants meeting soft or hard criteria for neurological presentations reached 12% in larger reviews [ 10 ]. Seizures of variable types are common among the more concrete neurological events [ 9 , 24 , 28 , 30 , 49 , 88 - 97 ]. As expected, some are particularly detailed as febrile seizures [ 24 ].…”
Section: Covid-19 Among Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with interest the article by Watroba and Bryda on a new-born male with SARS-CoV-2 associated meningo-encephalitis, post-inflammatory hydrocephalus and seizures [1]. Neuro-COVID in this patient was treated with a polypragmatic approach, including phenobarbital, acetazolamide, fluconazole, acyclovir, cefotaxime, and vancomycin [1]. The study is appealing but has limitations that raise concerns and should be discussed.…”
Section: Dear Editormentioning
confidence: 98%
“…A limitation of the study is that the infectious nature of meningo-encephalitis was not confirmed as the RT-PCR for SARS-CoV-2 was negative in the cerebrospinal fluid (CSF) [1]. We would like to know why the patient was diagnosed with meningo-encephalitis due to SARS-CoV-2 without evidence of a causative agent in the CSF.…”
Section: Dear Editormentioning
confidence: 99%